EFEKTIFITAS DAN KONSISTENSI ALAT PENUMBUK TERHADAP MUTU PAVING BLOCK - Dwi Deshariyanto; Moh. Kurnia Akbar (Fakultas Teknik, Universitas Wiraraja, 2020)
The production of paving blocks uses the manual method, where all the work is done full of human labor, making the process of making paving blocks relatively long and controlling the variations in collisions is also increasingly diverse. This then causes the consistency of the quality of paving blocks produced by this method to be poor. Need to create innovative new paving block production methods that can produce good paving block products in terms of quality. The basic concept of paving block production method innovation using gravity system. The method in making innovation of the paving block production method is to design and build a paving block pounder that can manage the weight collision consistency so that it can produce paving blocks with good quality. The composition used for the sample in the paving block pounder is with a mixture of 1 cement: 2.8 Stone Breaking Powder: 1.2 Black Sand. Data from the results of the study were analyzed using linear regression techniques to get the consistency value of the collision weight and the quality of the paving block. The results showed that the mechanical paving block pounder which utilizes gravitational energy has the consistency of the tool to the quality of the paving block in terms of its apparent nature, namely the test object there are no cracks and defects, the corners and the ribs are not easily tidied with the fingers. While the consistency value of the paving block pulverizer is judged by the compressive strength and absorption capacity of the paving block is still not good.